Development of Mind Mapping-Based Chemistry Pocketbook on Reaction Rate Material Class XI MIPA di SMAN 1 Candung - Nadia Sainita; Elvy Rahmi Mawarnis; Mimi Herman (Edusainstika: Jurnal Pembelajaran MIPA, 2023)
This study aims to obtain a valid and practical Mind Mapping-Based Chemistry Pocketbook on Reaction Rate Material for Class XI MIPA SMAN 1 Candung. This research applies Research and Development (R&D) with a 4D development model. The 4D model includes 4 phases, including: Define, Design, Develop, and Disseminate. However, the stages of research with this 4D model are only carried out until the development stage. The subjects in this study were students of class XI MIPA SMAN 1 Candung. Data were collected using research instruments including interview guidelines, validity sheets, and practicality sheets. Based on the results of data analysis, the average value of validity is 79.32% with a valid category and a practical value of 85.67% with a highly practical category.